The Role Of Organizational Culture In The Influence Of Knowledge Management Capability And Transformational Leadership On Organizational Performance In Manufacturing Companies - Hesti Lusvita; Agustinus Setyawan (UNIVED Press, 2026)
The increasingly competitive market conditions make many manufacturing companies, especially in Batam, initiate changes and adaptations in their business processes by implementing knowledge management capability, the Influence of transformational leadership, and the contribution of organizational culture, and all of them influence organizational performance. This study aims to determine the correlations between the variables mentioned and the extent to which these roles directly or indirectly affect organizational performance. Data collection was carried out quantitatively using the convenience sampling method with employees working in the manufacturing industry as respondents, who were then analyzed using PLS-SEM software. Furthermore, this finding proves the negative effect of the correlation between knowledge management capability and organizational performance. However, transformational leadership positively affects organizational performance. Organizational culture as a mediator also plays an important role in this finding as it significantly mediates both knowledge management capability and transformational leadership variables on organizational performance, respectively. These findings highlight the roles of the variables and how they influence each other so that ways can be found to maintain overall organizational performance. It is also recommended for future research to expand the demographic context to make the research more comprehensive.